2011
DOI: 10.1016/j.febslet.2011.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Real-time detection of central carbon metabolism in livingEscherichia coliand its response to perturbations

Abstract: Edited by Christian Griesinger Keywords:In vivo NMR Spectroscopy Metabolism Model organism Escherichia coli a b s t r a c tThe direct tracking of cellular reactions in vivo has been facilitated with recent technologies that strongly enhance NMR signals in substrates of interest. This methodology can be used to assay intracellular reactions that occur within seconds to few minutes, as the NMR signal enhancement typically fades on this time scale. Here, we show that the enhancement of 13 C nuclear spin polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
96
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 29 publications
1
96
0
1
Order By: Relevance
“…Spin-Lattice Relaxation Times (T 1 ) and the T 1 (1)/T 1 (2) Ratios for Carbon Signals in 13 C 6 -Glucose-d 7 (1) and a) Obtained from inversion recovery method using a 11.4T NMR spectroscopy. ized 1 using Escherichia coli and yeast reported by Meier and coworkers, [41][42][43][44] signals of several metabolites containing phosphorylated β-fructofuranoses generated through glycolysis, pentose phosphate pathway, and alcohol fermentation are detected. To analyze these metabolic differences in living microorganisms observed directly by feeding the hyperpolarized glucose can lead to understand the phenotypic and genotypic differences.…”
Section: Resultsmentioning
confidence: 99%
“…Spin-Lattice Relaxation Times (T 1 ) and the T 1 (1)/T 1 (2) Ratios for Carbon Signals in 13 C 6 -Glucose-d 7 (1) and a) Obtained from inversion recovery method using a 11.4T NMR spectroscopy. ized 1 using Escherichia coli and yeast reported by Meier and coworkers, [41][42][43][44] signals of several metabolites containing phosphorylated β-fructofuranoses generated through glycolysis, pentose phosphate pathway, and alcohol fermentation are detected. To analyze these metabolic differences in living microorganisms observed directly by feeding the hyperpolarized glucose can lead to understand the phenotypic and genotypic differences.…”
Section: Resultsmentioning
confidence: 99%
“…Since T 1 decay of 13 C polarization limits the duration of data acquisition, incorporation of 2 H prolongs the T 1 of 13 C in some molecules, enabling a longer period of observation [2]. Metabolism of hyperpolarized [U- 2 H 7 , U- 13 C 6 ]glucose to hyperpolarized [U- 13 C 3 ]lactate has been described in Escherichia coli [3], yeast [4], breast cancer cells [5] and lymphoma [6]. These findings are important because imaging of hyperpolarized lactate derived from glucose could provide a direct measure of glycolysis and thereby offer a fundamentally new method for investigating carbohydrate metabolism in vivo [6].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial metabolism has been previously investigated using HP 13 C glucose in E. coli 36 . In that study, the common fermentative byproduct, ethanol, was observed.…”
Section: Discussionmentioning
confidence: 99%